Pengaruh Berita Hoax Terhadap Kepercayaan Masyarakat Dalam Pemilu di Indonesia - TITONY TANJUNG; Gustrinanda, Rio (BULLET : Jurnal Multidisiplin Ilmu, 2023)
is a big phenomenon, the implementation of elections in developed and developing countries, elections are a means of people's sovereignty in choosing and also facilitating the change of power in a peaceful way, however the election process is carried out in various ways, from those carried out in an honest and fair way , until it is carried out in a way that is full of violations and fraud, in practice in the years of holding elections and elections which are commonly called political years, it is not uncommon for conflicts to occur between people which even result in hostilities in the community resulting from the emergence of cases of fake news (hoaxes). ) and hate speech. Law enforcement should be able to control the political situation and firmly give punishment to violators. Public trust in election results should be maintained by all parties who have an interest on the moral and ethical foundations that have long been instilled from generation to generation, so as to realize the implementation of independent, honest and fair elections as mandated by the election law. Through the study of the library research approach (library research) is the research method used in this study, by examining and exploring several journals, books and documents is a method used in collecting data, sources of data or information either in print or in the form electronics and others deemed relevant to the research